Influence of the labial gland's semiochemicals on the feeding behavior of Coptotermes havilandi (Isoptera: Rhinotermitidae) - Casarin, Fabiana Elaine [UNESP]; Arab, Alberto [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (My University, 2003)
In termites, food search is mediated by semiochemicals that are liberated by exocrine glands. In the present work we investigated the effect of the secretion of the labial glands of workers on the feeding behavior of Coptotermes havilandi. The secretion of the labial glands exhibited phagostimulant effect on the workers of this species. The soldiers showed a low activity in response to the labial gland extracts suggesting that this gland's secretion might inhibit the recruitment of soldiers. Behavioral evidence for the regulation of food consumption by workers was observed.
Keywords: Food consumption; Phagostimulant; Termites; Coptotermes; Coptotermes havilandi; Isoptera; Rhinotermitidae